Scaling functions and amplitude ratios for the Potts model on an uncorrelated scale-free network - Krasnytska, M. (Condensed Matter Physics, 2014)
We study the critical behaviour of the q-state Potts model on an uncorrelated scale-free network having a power-law node degree distribution with a decay exponent λ. Previous data show that the phase diagram of the model in the q,λ plane in the second order phase transition regime contains three regions, each being characterized by a different set of critical exponents. In this paper we complete these results by finding analytic expressions for the scaling functions and critical amplitude ratios in the above mentioned regions. Similar to the previously found critical exponents, the scaling functions and amplitude ratios appear to be λ-dependent. In this way, we give a comprehensive description of the critical behaviour in a new universality class.